The use of Factor Analysis Methods in Comparison of Regions - Kaminskienė, Bronislava; Misiūnas, Algimantas (Ekonomika, 2001)
The target of this work was to investigate the possibility to compare methods of component and factor analysis by regions. A common variable indicator, formed by applying methods of component and factor analysis, allows evaluating social and economic development level of counties. The value of economic development was compared with Gross domestic product per capita. Obtained similar findings show the fitness of mathematics-statistic models in use of regional comparative analysis.